Perturbations of Metabolomic Profiling of Spleen From Rats Infected With Clonorchis sinensis Determined by LC-MS/MS Method - Zhang, Xiaoli; Hu, Xinyi; Chen, Rui; Sun, Beibei; Gao, Yannan; Duan, Shanshan; Liu, Liyan; Han, Su (Frontiers in Molecular Biosciences, 2020)
Clonorchiasis is an important zoonotic parasitic disease worldwide. In view of the fact that parasite infection affects host metabolism, and there is an intricate relationship between metabolism and immunity. Metabolic analysis of the spleen could be helpful for understanding the pathophysiological mechanisms in clonorchiasis. A non-targeted ultra high performance liquid tandem chromatography quadrupole time of flight mass spectrometry (UHPLC-QTOF MS) approach was employed to investigate the metabolic profiles of spleen in rats at 4 and 8 weeks post infection with Clonorchis sinensis (C. sinensis). Then a targeted ultra-high performance liquid chromatography multiple reaction monitoring mass spectrometry (UHPLC-MRM-MS/MS) approach was used to further quantify amino acid metabolism. Multivariate data analysis methods, such as principal components analysis and orthogonal partial least squares discriminant analysis, were used to identify differential metabolites. Finally, a total of 396 and 242 significant differential metabolites were identified in ESI+ and ESI− modes, respectively. These metabolites included amino acids, nucleotides, carboxylic acids, lipids and carbohydrates. There were 38 significantly different metabolites shared in the two infected groups compared with the control group through the Venn diagram. The metabolic pathways analysis revealed that pyrimidine metabolism, aminoacyl-tRNA biosynthesis, purine metabolism and phenylalanine, tyrosine and tryptophan biosynthesis were significantly enriched in differential metabolites, which was speculated to be related to the disease progression of clonorchiasis. Furthermore, 15 amino acids screened using untargeted profiling can be accurately quantified and identifed by targeted metabolomics during clonrochiasis. These results preliminarily revealed the perturbations of spleen metabolism in clonorchiasis. Meanwhile, this present study supplied new insights into the molecular mechanisms of host-parasite interactions.